2016
DOI: 10.5146/tjpath.2016.01366
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microvessel density with prognostic factors in invasive ductal carcinomas of the breast

Abstract: Objective: Angiogenesis plays a key role in tumor growth and metastasis. Determination of microvessel density is the most common technique used to evaluate the amount of the intratumoral angiogenesis in breast cancer. We have aimed to investigate the relationship with tumor angiogenesis and prognostic parameters in breast invasive ductal carcinomas. Material and Method:In this study, a total of 100 invasive ductal carcinoma patients, who were diagnosed at the Department of Pathology, Ataturk university Faculty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 33 publications
7
17
1
Order By: Relevance
“…This is consistent with some published studies 46 -49 while some studies found no significant association between MVD and tumour size, and some studies reported an inverse association among them 50 -52 .When comparing MVD with involvement of axillary lymph nodes, we observed that MVD was higher in patients with positive axillary lymph nodes relative to patients without axillary lymph nodes (p=0.022). In similarity to our findings, several studies have found that high MVD is associated with metastases of the axillary lymph nodes 48,49,53,54 . Nonetheless, some other studies have also found no association between MVD and metastases of the axillary lymph node 50,55 .…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with some published studies 46 -49 while some studies found no significant association between MVD and tumour size, and some studies reported an inverse association among them 50 -52 .When comparing MVD with involvement of axillary lymph nodes, we observed that MVD was higher in patients with positive axillary lymph nodes relative to patients without axillary lymph nodes (p=0.022). In similarity to our findings, several studies have found that high MVD is associated with metastases of the axillary lymph nodes 48,49,53,54 . Nonetheless, some other studies have also found no association between MVD and metastases of the axillary lymph node 50,55 .…”
Section: Discussionsupporting
confidence: 92%
“…No statistically significant association was obtained between age, nodal status at diagnosis or stage of the tumour at diagnosis with stromal density. These findings were comparable to a study conducted by Ebru Sener et al 9 In the present study, 50 % cases were of Luminal A type followed by 26.9 % of cases to be of Luminal B type. In a study conducted by Marion Cortet et al 10 77.6 % cases were Luminal A type followed by 7.3 % Luminal B type.…”
Section: Comparison Of Stromal Density Of Carcinoma Breastsupporting
confidence: 92%
“…Turkish authors found the relationship between high MVD and increasing tumor size and lymph node involvement, but did not find any relationship between HER2 status and MVD in breast ductal carcinoma. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] The numerical value of tumor angiogenesis is defined as microvessel density (MVD). [ 5 ] It is measured by immunohistochemical (IHC) staining using antibodies such as CD 34 and others that are specific for vessel endothelium. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation